Pharmacological evaluation of selected atypical antipsychotics in an experimental model of Post-Traumatic Stress Disorder (PTSD) - Reddy, N. Ranga (IIT(BHU) Varanasi, 2018)
Abstract is available in content.
Keywords: Pharmacological; evaluation of selected atypical; antipsychotics